Strategi Pengembangan Usaha Mikro Kecil Menengah (UMKM) Kerupuk Sagu Di Desa Pulau Banjar Kari,Kecamatan Kuantan Tengah, Kabupaten Kuantan Singingi - Daffa Hauzan Nabil; Diana Rahmi; Julesfa Nursesmita; Annisa Dwi Elsa Refina; Nurhasanah Nurhasanah; Lili Gusnita; Habib Duanda; Putri Anjeli; Nindia Nindia; Halvy Gilang Kurniawan (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Sago cracker MSMEs still produce sago to the extent of the household industry, simple processing technology and lack of promotion of sago crackers. The research objective was to analyze the internal and external environment of sago cracker MSMEs, formulate and determine technical strategies and policies for the development of sugo cracker MSMEs in Kuanta Singingi Regency. This research was conducted by survey with quantitative and qualitative descriptive analysis. Qualitative descriptive using IFE and EFE matrix while qualitative descriptive wing SWOT method. The total internal factor evaluation (IFE) score was 2.6694 and the total external factor evaluation (EFE) score was 2.9857. The GE matrix results in sago cracker MSMEs located in quadrant (hold and maintain), namely market and product development. The resulting strategies for the development of sago cracker MSMEs are a MSMEs have a long-term development strategy by The experience of MSM owners has been on busmess for a long time, c) Policy and political support for the development of MSMEX d) MSMEs get guidance from the government, dy Participate in exhibitions and expus organized by the government both inside and outside the area. e) Product diversification and innovation by utilizing trend models in the community Marketing strategies to communities, inibes religions and other segments of society. ) Carrying out product mapping so that the product innovations produced cannot be imitated, h) Product penetration marketing strategies through discounts and price reductions, i) Digitalization strategy for marketing MSME products to reach a wider market. Develop partnerships between business actors in product and market development andk) Establishing partnerships with raw material suppliers